Effects of roof design on ceiling surface temperature - 457240 Saizul Azman Abdul Rani (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003